EFFECT OF AEROSOLS FROM BIOMASS BURNING OVER PRECIPITATION AND CLOUD FORMATION USING WRF/CHEM (CASE STUDY: RIAU FOREST FIRES OCTOBER 2015) - Indra Putra, Sany
Indonesia forest fires events release a large amount of aerosols and particulates to the atmosphere from peat (biomass) burned every year in dry season. The National Agency for Disaster Management (BNPB) in 2015 recorded that Riau was a province with widest burned area about 2643 Ha. Beside, our undestanding about the role of the aerosols in weather and climate is still very low. Therefore, it become crucial to gain more understanding in the interactions of aerosols to the environment, especially in cloud formation process. This research is aimed to understand the effect of aerosols from a forest fire that affected the environment and hypothetically inhibits cloud formation in way radiative and microphysics. The chemistry version of Weather Research Forecast (WRF/Chem) was used to modelling dispersion of aerosols in the atmosphere. Using emission Preprocessor PREP-CHEM-SOURCES to obtain emissions from the biomass burning as input data for the numeric model. The result of the simulation is that the emission from the forest fires giving negative feedback to the precipitation. MTSAT Satellite Imagery shows there is formations of little cloud that is not converted into a rain over the forest fires region. This result was supported by output from the model that shows that the aerosols have negative feedback to the cloud coverage.